GLOBULE LEUKOCYTES AND MAST CELLS IN BILE DUCTS OF SHEEP WITH CHRONIC FASCIOLIASIS - S. Mahmoud , G.; M. Shakir, M. (The Iraqi Journal of Veterinary Medicine, 1986)
Globule leukocytes were detected in the epithelial mucosa of the biliary system of sheep infected with liver flukes. Histochemical investigations revealed cytochemical similarities between the globule leukocytes and mast cells of the biliary system. Both the intracytoplasmic granules of the mast cells and the globules of the globule leukocytes contained a sulphated acidmucopolysacchride assosiated with a highly basic protein.